Consequences to patients, clinicians, and manufacturers when very serious adverse drug reactions are identified (1997–2019): A qualitative analysis from the Southern Network on Adverse Reactions (SONAR). (January 2021) - Bennett, Charles L.; Hoque, Shamia; Olivieri, Nancy; Taylor, Matthew A.; Aboulafia, David; Lubaczewski, Courtney; Bennett, Andrew C.; Vemula, Jay; Schooley, Benjamin; Witherspoon, Bartlett J.; Godwin, Ashley C; Ray, Paul S.; et al.
Abstract: Background: Adverse drug/device reactions (ADRs) can result in severe patient harm. We define very serious ADRs as being associated with severe toxicity, as measured on the Common Toxicity Criteria Adverse Events (CTCAE)) scale, following use of drugs or devices with large sales, large financial settlements, and large numbers of injured persons. We report on impacts on patients, clinicians, and manufacturers following very serious ADR reporting. Methods: We reviewed clinician identified very serious ADRs published between 1997 and 2019. Drugs and devices associated with reports of very serious ADRs were identified. Included drugs or devices had market removal discussed at Food and Drug Advisory (FDA) Advisory Committee meetings, were published by clinicians, had sales > 1 billion, were associated with CTCAE Grade 4 or 5 toxicity effects, and had either >1 billion in settlements or >1, 000 injured patients. Data sources included journals, Congressional transcripts, and news reports. We reviewed data on: 1) timing of ADR reports, Boxed warnings, and product withdrawals, and 2) patient, clinician, and manufacturer impacts. Binomial analysis was used to compare sales pre- and post-FDA Advisory Committee meetings. Findings: Twenty very serious ADRs involved fifteen drugs and one device. Legal settlements totaled 38.4 billion for 753, 900 injured persons. Eleven of 18 clinicians (61%) reported harms, including verbal threats from manufacturer (five) and loss of a faculty position (one). Annual sales decreased 94% from 29.1 billion pre-FDA meeting to 4.9 billion afterwards ( p <0.0018). Manufacturers of four drugs paid 1.7 billion total in criminal fines for failing to inform the FDA and physicians about very serious ADRs. Following FDA approval, the median time to ADR reporting was 7.5 years (Interquartile range 3, 13 years). Twelve drugs received Box warnings and one drug received a warning (median, 7.5 years following ADR reporting (IQR 5, 11 years). Six drugs and 1 device were withdrawn from marketing (median, 5 years after ADR reporting (IQR 4, 6 years)). Interpretation: Because very serious ADRs impacts are so large, policy makers should consider developing independently funded pharmacovigilance centers of excellence to assist with clinician investigations. Funding: This work received support from the National Cancer Institute (1R01 CA102713 (CLB), https://www.nih.gov/about-nih/what-we-do/nih-almanac/national-cancer-institute-nci ; and two Pilot Project grants from the American Cancer Society's Institutional Grant Award to the University of South Carolina (IRG-13–043–01) https://www.cancer.org/ (SH; BS).